Growth and Poverty Reduction in Armenia Achievements and Challenges - Beddies, Christian H. (International Monetary Fund, 2005)
Since 2000, Armenia's economic performance has been remarkable. Real economic growth has averaged 11 percent a year, annual inflation has averaged 3 percent, and poverty and inequality have fallen. The country has outperformed other low-income countries including other members of the Commonwealth of Independent States. This is particularly impressive given the geographical location of Armenia, the closure of two critical borders, and occasional political turmoil. The key factors behind Armenia's economic performance are prudent monetary and fiscal policies, liberal trade and foreign exchange regimes, rapid and relaively well-sequenced structural reforms, and support from the Armenian diaspora. In addition, the implementation of a poverty reduction strategy since 2002 has complemented the effect of economic growth on reducing poverty. This book assesses the country's economic transformation during the last 10 years and discusses the challenges to sustaining these successes